Understanding and controlling asthma in Latin America: A review of recent research informed by the SCAALA programme. Issue 3 (26th March 2023) - Cooper, Philip J.; Figueiredo, Camila A.; Rodriguez, Alejandro; dos Santos, Leticia Marques; Ribeiro‐Silva, Rita C.; Carneiro, Valdirene Leao; Costa, Gustavo; Magalhães, Thiago; dos Santos de Jesus, Talita; Rios, Raimon; da Silva, Hugo Bernardino F.; Costa, Ryan; et al.
Abstract: Asthma is an important health concern in Latin America (LA) where it is associated with variable prevalence and disease burden between countries. High prevalence and morbidity have been observed in some regions, particularly marginalized urban populations. Research over the past 10 years from LA has shown that childhood disease is primarily non‐atopic. The attenuation of atopy may be explained by enhanced immune regulation induced by intense exposures to environmental factors such as childhood infections and poor environmental conditions of the urban poor. Non‐atopic symptoms are associated with environmental and lifestyle factors including poor living conditions, respiratory infections, psychosocial stress, obesity, and a diet of highly processed foods. Ancestry (particularly African) and genetic factors increase asthma risk, and some of these factors may be specific to LA settings. Asthma in LA tends to be poorly controlled and depends on access to health care and medications. There is a need to improve management and access to medication through primary health care. Future research should consider the heterogeneity of asthma to identify relevant endotypes and underlying causes. The outcome of such research will need to focus on implementable strategies relevant to populations living in resource‐poor settings where the disease burden is greatest.